Integration of Islamic Guidance Service Model and Islamic Education Learning and its Effect on Students' Psychological Well-Being in the New Normal Era - Yunita Yunita (At-Ta'lim : Media Informasi Pendidikan Islam, 2023)
Abstract: Integration of Islamic Guidance Service Model and Islamic Education Learning and its Effect on Students' Psychological Well-Being in the New Normal Era This study aims to determine the integration of the Islamic guidance service and Islamic education model and its effect on the psychological well-being of students in the new normal era. The reseach used descriptive qualitative with field research methods. This research was conducted at SMA Kartika 1-2 Medan in 2021/2022. The subjects of this study were guidance and counseling teacher and Islamic education teacher. Data sources are obtained from interviews, documentation, and observation. The result show that the strategy used by guidance and counseling teacher and Islamic education teacher in fostering the psychological well-being of students uses a collaborative strategy, namely Islamic classical guidance. The conclusions show that the integration of the Islamic classical guidance teaching model by guidance and counseling teacher and Islamic education teacher at SMA Kartika 1-2 Medan was a collaborative method of the Islamic Education Guidance and Counseling approach.Abstrak: Integrasi Model Layanan Bimbingan Islami dan Pembelajaran PAI dan Pengaruhnya terhadap Kesejahteraan Psikologis Siswa di Era New NormalTujuan penelitian ini untuk mengetahui strategi kolaboratif yang dilakukan kguru agama islam dan konselor sekolahdalam menumbuhkan dan meningkatkan kesejahteraan psikologis siswa di era new normal. Pendekatan penelitian menggunakan kualitatif deskriptif, metode penelitian menggunakan field research. Penelitian ini dilaksanakan di SMA Kartika 1-2 Medan tahun 2021/2022. Subjek penelitian ini yaitu Kguru agama islam, Guru BK. Metode pengumpulan data menggunakan wawancara, dokumentasi dan observasi. Hasil penelitian menunjukkan integrasi model pengajaran bimbingan klasikal islami yang dilakukan kguru agama islam dan konselor sekolahdi SMA Kartika 1-2 Medan melalui pengajaran bimbingan klasikal islami memberikan pengaruh terhadap kesejahteraan psikologis siswa. Kesimpulan penelitian diperoleh temuan integrasi model pengajaran bimbingan klasikal islami yang dilakukan kguru agama islam dan konselor sekolahdi SMA Kartika 1-2 Medan merupakan metode kolaboratif pendekatan Bimbingan dan Konseling Pendidikan Islam